Determinants of directors' remuneration: Malaysian evidence 1998-2001 / Muhd Kamil Ibrahim, Norhazlina Ibrahim, Wan Adibah Wan Ismal... [et.al]. - Ibrahim, Muhd Kamil; Ibrahim, Norhazlina; Wan Ismal, Wan Adibah; Kamarudin, Khairul Anuar (Pusat Penerbitan Universiti (UPENA), 2005)
The objective of this study is to identify the factors associated with the directors' remunerations. The sample comprises 180 companies listed in the Kuala Lumpur Stock Exchange during the period 1989 to 2001. Instead of focussing on the pooled sample, this research also sub-sampled the firms based on economic condition in order to determine the effect of economic recession on the factors related to the directors 'remunerations. The findings show that the size of the firm, growth and industry are the significant explanatory variables of directors' remuneration. This research also found that the explanatory power of the independent variables is less during the time of economic recovery compared to the recovered period.